Analysis of pathogenic bacteria using exogenous volatile organic compound metabolites and optical sensor detection1. Issue 20 (6th March 2015) - Tait, Emma; Stanforth, Stephen P.; Reed, Stephen; Perry, John D.; Dean, John R.
<x xml:space="preserve">Abstract</x> A novel, low-cost and simple method for the detection of pathogenic bacteria is proposed.